Model migration for CFD and verification of a six-rotor UAV downwash - Yang, Shenghui; Tang, Qing; Zheng, Yongjun; Liu, Xingxing; Chen, Jian; Li, Xiaolong (International Journal of Agricultural and Biological Engineering, 2020)
Currently, Computational Fluid Dynamics (CFD) has been used to investigate agricultural UAV downwash. However, the validations of CFD models are difficult to deal with. Current verification methods are to use either water-sensitive papers or wind-speed arrays, which could get wind distribution or speed only. In this study, model migration was used to develop and verify downwash CFD models. The basic idea is to try to use the results of a scaled-down drone to represent that of a real-used UAV. The CFD models of both a real-used six-rotor UAV, JF01-10, and a 1:10 scaled-down small drone were developed by ANSYS. Then, the scaled-down drone was utilized to conduct trials by particle image velocimetry (PIV), so that not only distribution and speed but also flowing direction of downwash could be obtained. Results indicated the relative error between the PIV tests and the CFD models of the small UAV was less than 12%, while that between the tests and the CFD models of JF01-10 was less than 34%. It could be indicated that model migration could reflect multiple downwash characteristics but should be optimized in some complex details. This study was a preliminary but fundamental attempt to investigate CFD modelling and validation of agricultural UAVs and provided a novel thinking of downwash verification. Keywords: multi-rotor UAV, downwash, numerical simulation, computational fluid dynamics, verification, model migration DOI: 10.25165/j.ijabe.20201304.5569 Citation: Yang S H, Tang Q, Zheng Y J, Liu X X, Chen J, Li X L. Model migration for CFD and verification of a six-rotor UAV downwash. Int J Agric & Biol Eng, 2020; 13(4): 10–18.